2005
DOI: 10.1111/j.1365-3059.2005.01117.x
|View full text |Cite
|
Sign up to set email alerts
|

AFLP‐based PCR markers that differentiate spot and net forms of Pyrenophora teres

Abstract: Specific polymerase chain reaction (PCR) primers were developed from amplified fragment length polymorphism (AFLP) fragments of Pyrenophora teres , the causal agent of net blotch on barley leaves. The primers were designed specifically to amplify DNA from P. teres f. teres (net form) and allow its differentiation from P. teres f. maculata (spot form), which is morphologically very similar to P. teres f. teres in culture. The PCR amplification was carried out successfully from DNA extracted from fungal mycelium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 23 publications
3
29
0
3
Order By: Relevance
“…The markers used proved to be highly polymorphic and revealed clear differences in the distribution of alleles for 91 % of the loci tested between the two fungal types. This provides further evidence that the two formae specialis of P. teres are indeed genetically distinct from one another as has been shown in previous studies (Williams et al 2001;Leisova et al 2005a;Bakonyi & Justesen 2007;Keiper et al 2008). Because the forms of net blotch can be difficult to differentiate based on disease symptoms or spore morphology, the 14 STM markers that amplified distinct PTT-or PTM-specific allelic fragments can thus potentially be used as diagnostic markers for accurate disease diagnosis.…”
Section: Discussionmentioning
confidence: 61%
“…The markers used proved to be highly polymorphic and revealed clear differences in the distribution of alleles for 91 % of the loci tested between the two fungal types. This provides further evidence that the two formae specialis of P. teres are indeed genetically distinct from one another as has been shown in previous studies (Williams et al 2001;Leisova et al 2005a;Bakonyi & Justesen 2007;Keiper et al 2008). Because the forms of net blotch can be difficult to differentiate based on disease symptoms or spore morphology, the 14 STM markers that amplified distinct PTT-or PTM-specific allelic fragments can thus potentially be used as diagnostic markers for accurate disease diagnosis.…”
Section: Discussionmentioning
confidence: 61%
“…The amplification with four designed PCR primer pairs provided P. teres form-specific products. No cross-reaction was observed with DNA of several other species, such as P. tritici-repentis and P. graminea (Leisova et al 2005). Pyrenophora graminea is the causal agent of barley leaf stripe disease (Mokrani et al 2012).…”
Section: Molecular Phylogenymentioning
confidence: 91%
“…The data suggested that the RAPD technique can be used to tag genetic determinants for virulence in P. teres f. teres (Weiland et al 1999). Specific polymerase chain reaction (PCR) primers were developed from amplified fragment length polymorphism (AFLP) fragments of P. teres, in order to distinguish the two forms, P. teres f. teres (which cause net form blotch on barley leaves) and P. teres f. maculata (which causes spot form); the two forms are morphologically very similar in culture (Leisova et al 2005). The PCR assay was certified with 60 samples of Pyrenophora species.…”
Section: Molecular Phylogenymentioning
confidence: 99%
“…Wu et al (2003) using RFLP profiles were unable to separate the two forms and reported that the genetic distance between isolates of the two forms was similar to that of isolates among the same form. However, a recent report by Leisova et al (2005) based on AFLP data suggests that the two forms are distinct species.…”
Section: Introductionmentioning
confidence: 87%